The Robust Routing Protocol with Authentication for Wireless Adhoc Networks - Shakya, Subarna (Journal of ISMAC, 2020)
The adhoc networks are the platforms formed for specific reason to attain a specific purpose. It is a communication strategy followed by the wireless devices when or while the actual communication setup is not possible. Any portable device communicating in the wireless medium in a decentralized manner is termed to be a wireless adhoc network. One such device is the wireless-sensors that imitate the aforementioned procedures to send the information from the source to the target falls under the category of the wireless adhoc network, as it communicates through the air in a wireless medium. The rapid proliferation of sensors and growing demand for applications and services from the network formed using such wireless-sensors generate unrivaled appeals for routing data packets on infrastructure of the network formed using the wireless-sensors. Such sensors lays as the fundamental devices in a wide range application and are even more predominant in the internet of things paradigm. Numerous of such devices are used in the internet of things to gather enormous amount of data from a broad range of applications. The sensors used in the internet of thing usually performs the sensed data transmission to the gateway-nodes through the public channel that are insecure for conversing the confidential data. So the routing with authentication becomes essential, to make the routing robust and long lasting it is necessary to develop a light weight authentication scheme that does not consume too much of the energy of the network of the wireless-sensors. To handle this problem the paper concatenates the unique key generation technique the mid-square (MidS) with the Beziers curve based authentication (UKHA) to secure and authenticate the routing between the wireless-sensor networks framed in adhoc manner and the gate way nodes of the internet of things platform. The proposed protocol for routing is develop in the MATLAB and simulated in it to manifest the proficiency of the developed protocol on the terms of the energy consumption, packet deliver rate, percentage of losses incurred and running time.
Keywords: Wireless-Sensors; Internet of things; unique key Generation; Bezier Curve Authentication; Mid-Square Hash